DEEP PHENOTYPING OF THE G2019S LRRK2 MUTATION IN PARKINSON'S DISEASE: UCL COHORT. Issue 12 (15th November 2016) - Rizig, Mie; Jonvik, Hallgeir; Foltynie, Thomas; Limousin, Patricia; Bhatia, Kailash; Warner, Thomas; Morris, Huw; Wood, Nicholas
Abstract : The G2019S LRRK2 mutation is the commonest cause of autosomal dominant Parkinson's disease (PD). Modulating LRRK2 kinase activity is a potential route to therapy and LRRK2 inhibitors are in development. Aims: To recruit and characterise a cohort of "deep-phenotyped" LRRK2 G2019S carriers. Methods: Participants were recruited through UCLH neurogenetic services, neurologists, or self-referrals. Core data were collected using NINDS criteria including demographics, family history, time of onset, diagnostic criteria, imaging, levodopa response, motor and non-motor features, cognitive assessment, quality of life and environmental risk factors. Results: 28 symptomatic (mean age 63) and 8 relatives of whom 4 are pre-symptomatic carriers (mean age 46) were recruited. Half of the patients were Ashkenazi Jewish (AJ). Carriers from AJ background have a milder disease progression and an older age of onset (62 y vs 51 y). Dyskinesia, dopamine dysregulation and visual hallucinations were more frequent in males than females. Some patients have concurrent systemic disorders including Crohn's disease and arterial hypertension. Conclusion: In this UK cohort of LRRK2 cases, there are potentially important ethnic differences in LRRK2 phenotype and penetrance. This cohort will be used for comparison between LRRK2 and sporadic PD and will be useful for the development of future therapeutic trials.